2021
DOI: 10.3389/fcell.2021.614668
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Control of Mitochondrial Ca2+ Levels as a Survival Strategy of Cancer Cells

Abstract: Cancer cells have increased energy requirements due to their enhanced proliferation activity. This energy demand is, among others, met by mitochondrial ATP production. Since the second messenger Ca2+ maintains the activity of Krebs cycle dehydrogenases that fuel mitochondrial respiration, proper mitochondrial Ca2+ uptake is crucial for a cancer cell survival. However, a mitochondrial Ca2+ overload induces mitochondrial dysfunction and, ultimately, apoptotic cell death. Because of the vital importance of balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Our results in SH-SY5Y cells showed no detectable changes in MAMs after 2 h and 8 h of tunicamycin treatment in control or S1R knock-down cells ( Figure S3a,b ). The possible reasons for discrepancies with published data could be specificities of cell lines used, as most of the reported studies were performed in HeLa cells [ 5 , 25 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results in SH-SY5Y cells showed no detectable changes in MAMs after 2 h and 8 h of tunicamycin treatment in control or S1R knock-down cells ( Figure S3a,b ). The possible reasons for discrepancies with published data could be specificities of cell lines used, as most of the reported studies were performed in HeLa cells [ 5 , 25 ].…”
Section: Discussionmentioning
confidence: 98%
“…S1R seems to play a major role in this adaptation, since knock-down and a pharmacological antagonist of S1R almost eliminated respective responses ( Figure 2 b,c and Figure 3 b,e and Figure S2c ). In search for a possible mechanism of action of S1R, we measured the amount of MAMs, as it has been reported that MAMs are increasing during early or later stages of ER stress [ 5 , 25 ]. Our results in SH-SY5Y cells showed no detectable changes in MAMs after 2 h and 8 h of tunicamycin treatment in control or S1R knock-down cells ( Figure S3a,b ).…”
Section: Discussionmentioning
confidence: 99%
“…To approach this question, we came up with a strategy to buffer the Ca 2+ spiking through the L-type Ca 2+ channel by increasing the proximity between mitochondria and the sub-plasma membrane region. This was achieved by expressing the AKAP-RFP-CAAX construct [ 19 , 20 , 21 ] in INS-1 cells, which positioned mitochondria in the sub-PM region ( Figure 5 F, red images). By expressing AKAP-RFP-CAAX together with GFP-NFATc3 in Fura-2-loaded INS-1 cells, we monitored GFP-NFATc3 translocation and cytosolic Ca 2+ spiking simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…To do this, we came up with a hypothesis that if we buffer Ca 2+ spikes, which originate from L-type Ca 2+ channels at the plasma membrane, but keep the same ROS levels, we would not see the NFATc3 translocation and Ca 2+ oscillations. To test this idea, we positioned mitochondria to the sub-plasma membrane region using the AKAP-RFP-CAAX construct [ 19 , 20 , 21 ] to buffer local Ca 2+ spiking. Interestingly, AKAP-RFP-CAAX-expressing cells did not alter ROS production ( Figure S4a–d ) in response to near-UV light stimulation, but they eliminated near-UV light-induced Ca 2+ spiking as well as NFATc3 translocation ( Figure 5 B,E–G), thus supporting our hypothesis that ROS-induced cytosolic Ca 2+ spiking, and not ROS itself, is required for NFATc3 translocation to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Energy metabolism allows for the production of reactive oxygen species (ROS), leading to activation of pyk2 and src protein tyrosine kinases, which ultimately stimulates and promotes tumor development and invasion ( Xu et al, 2015 ). In cancer cells, the extra- and intracellular Ca 2+ pools accumulating in mitochondria influence the permeability of mitochondrial permeability transition pore (mtPTP), which thereby affects tumor cell apoptosis ( Qin et al, 2021 ; Madreiter-Sokolowski et al, 2021 ). (3) Mitochondria are related to multiple drug resistance: Genotoxic drugs trigger mitochondrial shift by means of regulating mitochondrial energy metabolism and upregulating mitochondrial oxidative phosphorylation, which results in drug resistance to chemotherapy ( Lee et al, 2017 ; Lee et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%